2021
DOI: 10.1186/s12877-020-01946-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the use of physical restraints in home care: development and feasibility testing of a multicomponent program to support the implementation of a guideline

Abstract: Background A validated evidence-based guideline was developed to reduce physical restraint use in home care. However, the implementation of guidelines in home care is challenging. Therefore, this study aims to systematically develop and evaluate a multicomponent program for the implementation of the guideline for reducing the use of physical restraints in home care. Methods Intervention Mapping was used to develop a multicomponent program. This met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Community care nurses and PCAs also reported that they had little influence if the client or their family decided to use devices such as bedrails or low beds, both forms of restraint, as they were only responsible for practices that occurred while they were present providing care. Similar barriers were reported in a Dutch qualitative study of restraint use in community settings that concluded that informal caregivers, especially relatives, have a dominant role in the use of restraint [ 40 ]. They also reported that relatives were less aware of the harms associated with restraint use and had limited knowledge of alternative strategies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Community care nurses and PCAs also reported that they had little influence if the client or their family decided to use devices such as bedrails or low beds, both forms of restraint, as they were only responsible for practices that occurred while they were present providing care. Similar barriers were reported in a Dutch qualitative study of restraint use in community settings that concluded that informal caregivers, especially relatives, have a dominant role in the use of restraint [ 40 ]. They also reported that relatives were less aware of the harms associated with restraint use and had limited knowledge of alternative strategies.…”
Section: Discussionsupporting
confidence: 71%
“…They also reported that relatives were less aware of the harms associated with restraint use and had limited knowledge of alternative strategies. Due to their findings, the researchers have instituted a training program on restraint for informal caregivers, with promising results to date [ 40 ]. Similar education and training may be needed in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…All three groups of professions score high in the following statement from NoMAD: “There are key people who drive DIPA forward and get others involved”. This could indicate a positive perception of the use of “implementation ambassadors” as a central part of the implementation process [ 29 , 30 , 31 ]. The laboratory technicians agree most with the statement.…”
Section: Discussionmentioning
confidence: 99%
“…An example of a systematic approach to plan a health promotion program is the study of Vandervelde et al (2021) on reducing the use of physical restraints in home care. The authors developed and evaluated a multicomponent program to support the implementation of a guideline [ 81 ]. By using intervention mapping, they ensured that the program was theoretical, empirical, and practical grounded.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, the authors obtained insight into the problem, the behaviour of healthcare professionals, the environment, and the determinants. Together with a stakeholder group, the authors selected theory and evidence-based methods to influence selected determinants; those methods were translated into practical applications (e.g., flyer, tutorials, ambassador for restraint-free home care) [ 81 ]. This review found that in falls prevention research, there is still a gap in the detailed description of implementation strategies and the effective use of implementation frameworks, models, and theories, making it difficult to know what does and does not work and to compare and replicate studies.…”
Section: Discussionmentioning
confidence: 99%